The PNPLA3‐I148M variant increases polyunsaturated triglycerides in human adipose tissue. (18th May 2020) - Qadri, Sami; Lallukka‐Brück, Susanna; Luukkonen, Panu K.; Zhou, You; Gastaldelli, Amalia; Orho‐Melander, Marju; Sammalkorpi, Henna; Juuti, Anne; Penttilä, Anne K.; Perttilä, Julia; Hakkarainen, Antti; Lehtimäki, Tiina E.; et al.
Abstract: Background & Aims: The I148M variant in PNPLA3 is the major genetic risk factor for non‐alcoholic fatty liver disease (NAFLD). The liver is enriched with polyunsaturated triglycerides (PUFA‐TGs) in PNPLA3‐I148M carriers. Gene expression data indicate that PNPLA3 is liver‐specific in humans, but whether it functions in adipose tissue (AT) is unknown. We investigated whether PNPLA3‐I148M modifies AT metabolism in human NAFLD. Methods: Profiling of the AT lipidome and fasting serum non‐esterified fatty acid (NEFA) composition was conducted in 125 volunteers ( PNPLA3 148MM/MI, n = 63; PNPLA3 148II, n = 62). AT fatty acid composition was determined in 50 volunteers homozygous for the variant ( PNPLA3 148MM, n = 25) or lacking the variant ( PNPLA3 148II, n = 25). Whole‐body insulin sensitivity of lipolysis was determined using [ 2 H5 ]glycerol, and PNPLA3 mRNA and protein levels were measured in subcutaneous AT and liver biopsies in a subset of the volunteers. Results: PUFA‐TGs were significantly increased in AT in carriers versus non‐carriers of PNPLA3‐I148M. The variant did not alter the rate of lipolysis or the composition of fasting serum NEFAs. PNPLA3 mRNA was 33‐fold higher in the liver than in AT ( P < .0001). In contrast, PNPLA3 protein levels per tissue protein were three‐fold higher in AT than the liver ( P < .0001) and nine‐fold higher when related to whole‐body AT and liver tissue masses ( P < .0001). Conclusions: Contrary to previous assumptions, PNPLA3 is highly abundant in AT. PNPLA3‐I148M locally remodels AT TGs to become polyunsaturated as it does in the liver, without affecting lipolysis or composition of serum NEFAs. Changes in AT metabolism do not contribute to NAFLD in PNPLA3‐I148M carriers.